Kepemimpinan Berbasis Advokasi Perempuan sebagai Upaya Melawan Diskriminasi Gender - Mariance Mariance; Veraciouus Veraciouus; Novita Rura (STIKAS Santo Yohanes Salib Kalimantan Barat, 2026)
This research aims to offer leadership based on women's advocacy as an effort to fight gender discrimination. Gender discrimination is currently increasingly prevalent and has a negative impact on women. One of the causes of gender discrimination that has not been completely resolved is the leadership factor. The focus and attention of leaders in carrying out their roles has not been fully directed towards the problems experienced by women. This research uses descriptive qualitative research methods. Literature study was used to find the information needed in this research. Leadership based on women's advocacy aims to fight for women's rights in gender equality and overcome discrimination. In leadership based on women's advocacy, it can be done in various ways, namely a leader needs to have in-depth knowledge about gender equality and be committed to being a driver of social change and upholding human rights. Apart from that, leaders also need to pay full attention to women as a form of hospitality, renewing the community in knowledge about gender equality and implementing women's recovery and empowerment. The hope is that through women's advocacy-based leadership, we will lead to a society that is gender equal and free from injustice and discrimination.